Influence of agrochemicals on moisture stress mitigation in Indian mustard under rainfed conditions of Jammu - BHARAT, RAJEEV; ARYA, VIVAK M.; SHARMA, VIKAS; KOUR, S.; GUPTA, MEENAKSHI; SHARMA, V.; RAI, S. K.; GUPTA, R. (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted at the Research farm, Chatha, Jammu during the rabi season of 2011- 12 and 2012-13 to evaluate the performance of different agrochemicals viz. urea, thio-urea and potassium nitrate on moisture stress mitigation in Indian Mustard (Brassica juncea) under rainfed conditions of Jammu. The application of 0.05% thio-urea spray twice at 50 % flowering stage followed by 50 % siliqua filing stage though at par with twice application of 1% KNO3 spray at 50 % flowering stage followed by 50 % siliqua filing stage resulted in significant increase in the seed yield as well as rainwater use efficiency (RUE) and cumulative water use (CWU) in Indian mustard. However, 0.05% thio-urea spray at 50 % flowering stage followed by 50 % siliqua filing stage) was found to be the most economical treatment than other treatments in comparison.